PEMANFAATAN APLIKASI EXAM BROWSER DALAM PELAKSANAAN PAS BERBASIS DIGITAL DI MA BILINGUAL KOTA BATU MALANG - Ahmad Ainur Rofiq; Fifin Afriana Farindi Astutik; Dewi Mashito; Indah Aminatuz Zuhriyah (Universitas Yudharta Pasuruan, 2023)
In learning activities, a method is needed to measure learning achievement, academic ability and absorption of students during one semester of learning. The end of semester assessment also serves as feedback for madrasas as a reference for learning in the following semester. At this time we are in the era of digitalization which requires us to be able to adapt to technological advances. This study used exploratory qualitative research with descriptive research methods, the subjects in this study were proctors, Islamic Islamic Education teachers and students at MA Billingual Batu Malang. Evaluation using the exambrowser is a solution for educators in evaluating learning using digital technology. This paper examines how the use of the exam browser is used in the final school assessment process at Madrasah Aliyah Bilingual Batu Malang. The findings in this study show that the exambrowser application is very effective to implement because it has a high level of security which makes students unable to access other applications during the final semester assessment.